Flexible perovskite solar cell preparation method and flexible perovskite solar cell

By using ferrite stainless steel foil substrate and borate modification materials in flexible perovskite solar cells, the problems of uneven stress and poor adhesion of the film layer are solved, and efficient and stable preparation of flexible perovskite solar cells are achieved. , suitable for large-scale production.

CN119136629APending Publication Date: 2024-12-13CNNC OPTOELECTRONICS TECH (SHANGHAI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411252682.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The stability and efficiency of flexible perovskite solar cells are insufficient, the mechanical properties are poor, and the high-temperature annealing treatment of the inorganic charge transport layer is difficult to achieve uniformity on the polymer substrate, resulting in uneven stress and poor adhesion of the film layer.

Method used

Ferrite stainless steel foil is used as a flexible substrate, and borate modification material is added to the interface on the perovskite film layer. Each layer is deposited by magnetron sputtering and solution method, and combined with ultraviolet activation treatment and vacuum evaporation method, the anti-resistance is prepared. Flexible perovskite solar cell with strong bending ability and good mechanical properties.

Benefits of technology

It improves the bending resistance and mechanical properties of flexible perovskite solar cells, enhances their high temperature resistance and stability, simplifies the preparation process, reduces energy consumption, and is suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119136629A_ABST
    Figure CN119136629A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible perovskite solar cell preparation method and a flexible perovskite solar cell, and the method comprises the steps: carrying out the coating pretreatment of a ferritic stainless steel foil substrate, and depositing a bottom electrode on the ferritic stainless steel foil substrate; after ultraviolet activation treatment before film coating is carried out on a bottom electrode, a hole transport layer is deposited on the activated bottom electrode; preparing a perovskite light absorption layer on the hole transport layer; coating the upper interface of the perovskite light absorption layer with a borate solution with a preset concentration in a slit manner according to a preset condition, and preparing a borate modification layer; preparing an electron transport layer on the borate modified layer; and preparing a top electrode on the electron transport layer to obtain the flexible perovskite solar cell. The excellent mechanical property of the ferrite stainless steel foil substrate and the absorption of the borate modification material on the stress of the film layer are effectively utilized, and the excellent light absorption property of the perovskite material is combined, so that the photovoltaic module with high bending resistance and good mechanical property is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of perovskite solar cells, and in particular to a method for preparing a flexible perovskite solar cell and a flexible perovskite solar cell. Background Art

[0002] As the solar cell technology with the most promising industrial application prospects today, organic-inorganic hybrid perovskite solar cells have the advantages of high efficiency, low raw material prices, and strong adaptability to different substrate materials. Compared with batteries based on rigid materials such as glass, which generally have problems such as heavy weight and easy brittle fracture, flexible substrates have many advantages such as light weight and wide application scenarios, and their industrialization prospects are broader.

[0003] However, the commercial application of large-area flexible perovskite solar cells is difficult to popularize at present. The main problems are the insufficient stability and efficiency of flexible perovskite cells, as well as poor mechanical properties. The inconsistent elastic modulus between the film layers leads to uneven stress distribution between the film layers, poor film adhesion, and insufficient overall bending resistance.

[0004] In order to enable flexible perovskite solar cells to obtain better high temperature resistance, efficiency and stability, the use of organic charge transport layers should be eliminated and replaced by inorganic charge transport layers. However, inorganic charge transport layers generally require high temperature annealing treatment, and polymer flexible substrate materials such as PET, PEN, and PI cannot withstand high stability. In addition, during the roll-to-roll large-area coating preparation process, the polymer substrate is easily stretched and deformed unevenly, affecting the bonding strength of each film layer. Summary of the invention

[0005] In view of this, the present application proposes a method for preparing a flexible perovskite solar cell and a flexible perovskite solar cell to solve the above problems.

[0006] According to one aspect of the present application, a method for preparing a flexible perovskite solar cell is provided, comprising the following steps:

[0007] After the ferritic stainless steel foil substrate is subjected to a pre-plating treatment, a bottom electrode is deposited on the ferritic stainless steel foil substrate;

[0008] After the bottom electrode is subjected to UV activation treatment before coating, a hole transport layer is deposited on the activated bottom electrode;

[0009] Preparing a perovskite light absorbing layer on the hole transport layer;

[0010] Slit coating a borate solution of a preset concentration on the upper interface of the perovskite light absorbing layer according to preset conditions to prepare a borate modified layer;

[0011] preparing an electron transport layer on the borate modified layer;

[0012] A top electrode is prepared on the electron transport layer to obtain a flexible perovskite solar cell.

[0013] As an optional embodiment of the present application, optionally, in the borate solution, the borate is any one of MgB2O4, CaB2O4 and its hydrates, LiBO2, Li2B4O7, K2B4O7 and its hydrates, and the solvent is chlorobenzene.

[0014] As an optional embodiment of the present application, optionally, the preset concentration is 0.5-2 mg / ml.

[0015] As an optional implementation scheme of the present application, optionally, the preset conditions include:

[0016] The injection speed is 0.05-0.15ml / min, the coating gap is 0.2mm, and the coating head moving speed is 10mm / s.

[0017] As an optional embodiment of the present application, optionally, after slit coating a borate solution on the upper interface of the perovskite light absorbing layer according to preset conditions to prepare a borate modified layer, the method further includes:

[0018] The borate modified layer was annealed in an oven and then taken out.

[0019] As an optional embodiment of the present application, optionally, the material of the ferritic stainless steel foil flexible substrate is 1Cr17 ferritic stainless steel foil.

[0020] As an optional embodiment of the present application, optionally, the material of the bottom electrode and the top electrode are either ITO or FTO;

[0021] The material of the hole transport layer is NiOx;

[0022] The material of the perovskite light absorbing layer is CH3NH3PbI 3-x Cl x .

[0023] The material of the electron transport layer is a mixture of C60 and BCP.

[0024] According to another aspect of the present application, a flexible perovskite solar cell is provided, which is prepared by using any of the above-mentioned methods for preparing a flexible perovskite solar cell, comprising:

[0025] The ferritic stainless steel foil flexible substrate, bottom electrode, hole transport layer, perovskite light absorption layer, borate modification layer, electron transport layer and top electrode are arranged in sequence from bottom to top.

[0026] As an optional embodiment of the present application, optionally, the thickness of the ferritic stainless steel foil substrate is 35-50 μm;

[0027] The thickness of the bottom electrode is 150-450nm;

[0028] The thickness of the hole transport layer is 10-50 nm;

[0029] The thickness of the perovskite light absorbing layer is 300-500nm;

[0030] The thickness of the borate modified layer is 5-20 nm;

[0031] The thickness of the electron transport layer is 10-30 nm;

[0032] The thickness of the top electrode is 150-400 nm.

[0033] Beneficial effects of this application:

[0034] The method of the present application effectively utilizes the excellent mechanical properties of the ferrite stainless steel foil substrate and the absorption of the film stress by the borate modified material, and combines the excellent light absorption properties of the perovskite material to prepare a photovoltaic module with strong bending resistance and good mechanical properties, which is suitable for large-scale industrial production, and then prepares a large-area flexible battery module, which is more cost-effective than the manufacture of traditional solar cells such as copper indium gallium selenide, cadmium telluride, and crystalline silicon. In addition, the method of the present application has a simple preparation process, low energy consumption, good process repeatability, and can be industrialized to mass-produce flexible solar cell modules.

[0035] Other features and aspects of the present application will become apparent from the following detailed description of exemplary embodiments with reference to the attached drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate exemplary embodiments, features, and aspects of the present application and, together with the description, serve to explain the principles of the present application.

[0037] Figure 1 A flow chart showing a method for preparing a flexible perovskite solar cell according to the present invention is shown;

[0038] Figure 2 A schematic diagram showing the structure of a flexible perovskite solar cell of the present invention is shown;

[0039] Figure 3 A schematic diagram of a bending test of a battery assembly of the present invention is shown;

[0040] Figure 4 The IV test results after bending of Example 1 of the present invention are shown;

[0041] Figure 5 The IV test results after bending of Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION

[0042] Various exemplary embodiments, features and aspects of the present application will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0043] Among them, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential" and the like indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present application or simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the present application.

[0044] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0045] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0046] In addition, in order to better illustrate the present application, numerous specific details are given in the following specific embodiments. It should be understood by those skilled in the art that the present application can also be implemented without certain specific details. In some examples, methods, means, components and circuits well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present application.

[0047] Ferritic stainless steel foil has good high temperature resistance and tensile strength, so this application uses ferritic stainless steel foil as the substrate of perovskite solar cells, which helps flexible perovskite solar cells achieve higher efficiency and stability. In addition, this application also adds borate modification materials to the interface of the perovskite film layer, which can release the stress between the film layers and effectively improve the bending resistance of the component.

[0048] like Figure 1As shown, on one hand, the present application provides a method for preparing a flexible perovskite solar cell, comprising the following steps:

[0049] S100, depositing a bottom electrode on the ferritic stainless steel foil substrate after performing a pre-plating treatment on the ferritic stainless steel foil substrate;

[0050] In this step, ferritic stainless steel foil is used as the substrate of the flexible perovskite solar cell, and before the bottom electrode is deposited on the ferritic stainless steel substrate, the ferritic stainless steel foil substrate needs to be pre-treated for coating. Specifically, the pre-treatment is to ultrasonically clean the ferritic stainless steel foil substrate in anhydrous ethanol at 40°C for 1 hour, then ultrasonically clean it twice with deionized water, each time for 10 minutes, and finally dry it in a 70°C oven for about 1 hour before taking it out. It can effectively remove impurities such as grease and oil on the surface of the ferritic stainless steel foil to ensure that the coating can be evenly and firmly attached to the substrate, and the cleaned ferritic stainless steel foil is dried to avoid the introduction of moisture or other impurities in the subsequent coating process.

[0051] Furthermore, the bottom electrode is deposited on the ferritic stainless steel foil substrate after pretreatment by magnetron sputtering. Wherein, the material of the bottom electrode is preferably any one of ITO or FTO. Specifically, when the vacuum degree of the magnetron sputtering chamber is lower than 0.00002Torr, sputtering of any one of ITO or FTO begins, wherein the sputtering power is 200w, the sputtering time is 10min, the moving linear speed of the ferritic stainless steel foil substrate is 0.5-0.6m / min, the argon gas flow rate is 20sccm, and the argon gas pressure is 3mTorr, thereby achieving the deposition of the bottom electrode. Wherein, the magnetron sputtering method is used to deposit the bottom electrode, which can make the bonding force between the bottom electrode and the substrate stronger, and the deposited bottom electrode is also more uniform.

[0052] S200, after the bottom electrode is subjected to UV activation treatment before coating, a hole transport layer is deposited on the activated bottom electrode;

[0053] In this step, the hole transport layer continues to be deposited on the bottom electrode, wherein before deposition, the bottom electrode needs to be subjected to UV activation treatment before coating. Specifically, the bottom electrode is placed in the drawer of a UV light cleaning machine with one side facing up. The UV light irradiation time is 15 minutes, and the main wavelength of the UV light is 430nm, the power of the UV lamp is 250W, and the UV light irradiation height is 20-40mm. During the UV activation treatment, the surface of the bottom electrode is modified by the photochemical action of ultraviolet rays. Ultraviolet rays can destroy the chemical bonds on the surface of the bottom electrode and form new active sites, thereby increasing the wettability and reactivity of the surface. As a result, the bonding force and uniformity between the coating and the bottom electrode can be effectively improved during the subsequent coating process.

[0054] Furthermore, a hole transport layer is deposited on the bottom electrode after activation treatment by magnetron sputtering. Among them, the material of the hole transport layer is preferably NiOx. Specifically, when the vacuum degree of the magnetron sputtering chamber is lower than 0.00002Torr, NiOx is sputtered, the sputtering power is 140-160W, the sputtering time is 10min, the moving linear speed of the ferritic stainless steel foil is 0.5-0.6m / min, the working gas is argon and oxygen mixture, the gas flow rate is 20sccm, and the gas pressure is 2mTorr. After the preparation of the hole transport layer NiOx is completed, it is placed in a 300°C oven for annealing for 1h, and then taken out after cooling to room temperature with the furnace. Among them, magnetron sputtering increases the ionization rate of electrons by using a magnetic field to restrain the movement of electrons in a high vacuum environment, so that the desired hole transport layer is finally deposited on the bottom electrode.

[0055] S300, preparing a perovskite light absorbing layer on the hole transport layer;

[0056] In this step, a perovskite light absorbing layer is prepared on the hole transport layer by a solution method. The material of the perovskite light absorbing layer is preferably CH3NH3PbI 3-x Cl x The solvent is preferably DMF. Specifically, 0.8-1.5M CH3NH3PbI 3-x Cl x The solution, the solvent is DMF, and the injection speed is 0.1-0.2ml / min, the coating gap is 0.2mm, and the coating head moving speed is 7mm / s. The prepared perovskite film layer is then annealed in a 150°C oven for 10min. Among them, the perovskite absorption layer is prepared by a solution method, that is, a uniform thin film is formed on the hole transport layer by slit coating using a perovskite precursor material dissolved in a solvent to prepare a perovskite light absorbing layer.

[0057] S400, slit coating a borate solution of a preset concentration on the upper interface of the perovskite light absorbing layer according to preset conditions to prepare a borate modified layer;

[0058] In this step, a borate modified layer is prepared on the upper interface of the perovskite light absorbing layer by a solution method. That is, in the process of preparing a flexible perovskite solar cell, the efficiency and stability are improved by adding a modified material between the functional layers of the perovskite solar cell. And in order to reduce the stress between the film layers and improve the mechanical properties of the component, this step is achieved by adding a borate modified material to the upper interface of the perovskite film layer. The borate modified material can release the stress between the film layers and effectively improve the bending resistance of the component. That is, the upper interface of the perovskite functional layer is modified by a borate additive, which effectively releases the stress in all directions of the perovskite film layer, thereby preparing a flexible perovskite solar cell with strong bending resistance and good mechanical properties.

[0059] S500, preparing an electron transport layer on the borate modified layer;

[0060] In this step, the electron transport layer is prepared on the borate modified layer by vacuum evaporation. Specifically, when the vacuum degree of the vacuum chamber is lower than 5*10 -4 Deposition begins at 1000 A / s with a deposition rate of 0.2 A / s. It should be noted that the electron transport layer is preferably a mixture of C60 and BCP, and during the deposition process, the electron transport layer C60 is first deposited with a corresponding deposition thickness of 5-15 nm, and then the electron transport layer BCP is deposited with a corresponding deposition thickness of 5-15 nm. Among them, the vacuum evaporation method can achieve uniform evaporation of materials under a high vacuum environment, ensuring that the electron transport layer forms a uniform and dense film on the borate modified layer, thereby improving the photoelectric conversion efficiency and stability of the device.

[0061] S600, preparing a top electrode on the electron transport layer to obtain a flexible perovskite solar cell.

[0062] In this step, a top electrode is prepared on the electron transport layer by magnetron sputtering. The material of the top electrode is preferably any one of ITO or FTO. Specifically, when the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, sputtering of any one of ITO or FTO begins, and the sputtering power is 150W, the sputtering time is 5min, and then the sputtering power is 200W, and the sputtering time is 5min. The preparation of the flexible perovskite solar cell is completed.

[0063] The method of the present application effectively utilizes the excellent mechanical properties of the ferrite stainless steel foil substrate and the absorption of the film stress by the borate modified material, and combines the excellent light absorption properties of the perovskite material to prepare a photovoltaic module with strong bending resistance and good mechanical properties, which is suitable for large-scale industrial production, and then prepares a large-area flexible battery module, which is more cost-effective than the manufacture of traditional solar cells such as copper indium gallium selenide, cadmium telluride, and crystalline silicon. In addition, the method of the present application has a simple preparation process, low energy consumption, good process repeatability, and can be industrialized to mass-produce flexible solar cell modules.

[0064] As an optional embodiment of the present application, optionally, in the borate solution, the borate is any one of MgB2O4, CaB2O4 and its hydrates, LiBO2, Li2B4O7, K2B4O7 and its hydrates, and the solvent is chlorobenzene.

[0065] As an optional embodiment of the present application, optionally, the preset concentration is 0.5-2 mg / ml.

[0066] It should be noted that the method of the present application adopts a solution method to prepare a silicate modified layer on the upper interface of the perovskite light-absorbing layer. The upper interface of the perovskite functional layer is modified by a borate additive, which can effectively release the stress in all directions of the perovskite film layer, thereby preparing a flexible perovskite solar cell with strong anti-bending ability, good mechanical properties, excellent efficiency and stability. The concentration of the borate solution slit-coated on the upper interface of the perovskite light-absorbing layer is preferably 0.5-2 mg / ml. In the borate solution, the borate is preferably any one of MgB2O4, CaB2O4 and CaB2O4 hydrate, LiBO2, Li2B4O7, K2B4O7 and K2B4O7 hydrate, and the solvent is chlorobenzene, which can dissolve the borate to form a uniform solution.

[0067] As an optional implementation scheme of the present application, optionally, the preset conditions include: injection speed 0.05-0.15 ml / min, coating gap 0.2 mm, coating head movement speed 10 mm / s.

[0068] It should be noted that the preferred injection speed of the present application is 0.05-0.15 ml / min, in order to ensure that the solution can flow out stably and evenly during the coating process, avoiding the problem of uneven coating caused by too fast or too slow. At the same time, in order to form a uniform borate modification layer on the perovskite light-absorbing layer, the preferred coating gap of the present application is 0.2 mm to ensure the thickness and uniformity of the modification layer. Not only that, the movement speed of the coating head of the present application is preferably 10 mm / s, which matches the injection speed, ensuring that the solution can be evenly and continuously covered on the perovskite light-absorbing layer during the coating process.

[0069] As an optional embodiment of the present application, optionally, after preparing the borate modification layer by slit coating a borate solution on the upper interface of the perovskite light absorbing layer according to preset conditions, the method further includes: annealing the borate modification layer in an oven and then taking it out.

[0070] It should be noted that in order to form a better combination between the borate modification layer and the perovskite light-absorbing layer and improve the performance of the modification layer, the borate modification layer needs to be taken out after annealing in the oven. Specifically, it is preferably taken out after annealing in an oven at 150°C for 15 minutes, thereby preparing a better borate modification layer, thereby improving the performance and stability of the finished perovskite solar cell.

[0071] As an optional embodiment of the present application, optionally, the material of the ferritic stainless steel foil flexible substrate is 1Cr17 ferritic stainless steel foil.

[0072] It should be noted that in order to enable flexible perovskite solar cells to obtain better high temperature resistance, efficiency and stability, this application selects ferritic stainless steel foil with good high temperature resistance and tensile strength as the flexible substrate, and the preferred material is 1Cr17 ferritic stainless steel foil to improve the efficiency, stability and mechanical properties of flexible perovskite solar cells.

[0073] As an optional embodiment of the present application, optionally, the materials of the bottom electrode and the top electrode are either ITO or FTO; the material of the hole transport layer is NiOx; the material of the perovskite light absorption layer is CH3NH3PbI 3-x Cl x The material of the electron transport layer is a mixture of C60 and BCP.

[0074] In this embodiment, the bottom electrode and the top electrode are preferably ITO or FTO with high light transmittance and small square resistance, so that light can be incident from the top electrode side of the battery. The electron transport layer is a blend of C60 and BCP. In the process of depositing the electron transport layer, C60 is deposited first, and then BCP is deposited, so that the electron transport layer is deposited on the borate modified layer.

[0075] It can be seen that the flexible perovskite solar cell of the present application aims at the shortcomings of the existing polymer flexible substrate perovskite solar cells, and prepares a flexible perovskite solar cell with ferrite stainless steel foil as the substrate. Specifically, Figure 2 As shown, a ferritic stainless steel foil flexible substrate is used, and light is incident from the top electrode side of the battery. The flexible battery structure is, from bottom to top, a ferritic stainless steel foil flexible substrate 1, a bottom electrode 2, a hole transport layer 3, a perovskite absorption layer 4, a borate modified layer 5, an electron transport layer 6, and a top electrode 7. Among them, ferritic stainless steel foil has good mechanical properties, high temperature resistance, and is not easily deformed when stretched. Therefore, as a flexible perovskite solar cell substrate, it can effectively overcome the current problems of flexible perovskite cells being not resistant to high temperatures, poor stability, insufficient bending resistance, and poor mechanical properties, as well as the problems of traditional rigid perovskite solar cells being heavy, large in size, unable to bend, narrow in application range, and difficult to transport. In addition, the present application also adds a borate modified material to the upper interface of the perovskite film layer, and uses a borate to add and modify the upper interface of the perovskite functional layer, effectively releasing the stress in all directions of the perovskite film, thereby preparing a flexible perovskite solar cell with strong bending resistance and good mechanical properties.

[0076] The following provides Example 1 and Comparative Example 1 to illustrate the method of the present application in detail.

[0077] Example 1

[0078] A method for preparing a flexible perovskite solar cell comprises the following steps:

[0079] (1) The ferritic stainless steel foil substrate was ultrasonically cleaned in anhydrous ethanol at 40° C. for 1 h, and then ultrasonically cleaned twice with deionized water, each time for 10 min, and finally dried in an oven at 70° C. for about 1 h and then taken out for use;

[0080] (2) Loading the substrate into the magnetron sputtering equipment, and starting to sputter ITO when the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, the sputtering power is 200 W, the sputtering time is 10 min, the component moving linear speed is 0.5-0.6 m / min, the argon gas flow rate is 20 sccm, and the argon gas pressure is 3 mTorr, completing the preparation of the bottom electrode;

[0081] (3) Place the bottom electrode with one side facing up in the drawer of a UV light cleaning machine. The UV light irradiation time is 15 minutes. The main wavelength of the UV light is 430nm. The power of the UV lamp is 250W. The UV light irradiation height is 20-40mm. Complete the UV activation treatment before the bottom electrode is coated.

[0082] (4) When the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, NiOx sputtering is started, the sputtering power is 140-160W, the sputtering time is 10min, the component moving linear speed is 0.5-0.6m / min, the working gas is argon and oxygen mixture (oxygen accounts for 1%), the gas flow rate is 20sccm, the gas pressure is 2mTorr, and the preparation of the hole transport layer is completed. Hole transport layer NiO x After preparation, the component was placed in a 300°C oven for annealing for 1 h, then cooled to room temperature with the furnace and taken out;

[0083] (5) Slit-coat 0.8-1.5M CH3NH3PbI on the hole transport layer 3-x Cl x Perovskite solution, solvent is DMF, injection speed is 0.1-0.2ml / min, coating gap is 0.2mm, coating head moving speed is 7mm / s, and then the prepared perovskite film layer is annealed in an oven at 150℃ for 10min;

[0084] (6) Slit coating a 0.5-2 mg / ml borate solution on the perovskite light absorbing layer, wherein the borate is one of MgB2O4, CaB2O4 and its hydrate, LiBO2, Li2B4O7, K2B4O7 and its hydrate, the solvent is chlorobenzene, the injection speed is 0.05-0.15 ml / min, the coating gap is 0.2 mm, and the coating head movement speed is 10 mm / s. Then, the prepared borate modified layer is annealed in an oven at 150° C. for 15 min and then taken out;

[0085] (7) Place the component in the chamber of a thermal evaporation deposition device, and start deposition when the vacuum degree of the vacuum chamber is lower than 5*10-4Pa, with a deposition rate of 0.2A / s. First, deposit the electron transport layer C60 with a deposition thickness of 5-15nm. Then, deposit the electron transport layer BCP with a deposition thickness of 5-15nm;

[0086] (8) Place the component in a magnetron sputtering chamber. When the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, start sputtering ITO or FTO. The sputtering power is 150 W for 5 minutes, and then 200 W for 5 minutes. The component preparation is now complete.

[0087] Example 1 Test:

[0088] (1) Figure 3 As shown, the battery assembly of Example 1 is placed on a cylinder with a diameter of 50 and bent 100 times;

[0089] (2) The battery efficiency was tested using a Keithley 2450 digital source meter. The sweep voltage was set to 1.2 to -0.1 V, with a step of 0.1 V and an interval of 10 ms. The results are as follows: Figure 4 As shown, the open circuit voltage of the battery is 1.12V and the short circuit current density is 9.73mA / cm 2 , the filling factor is 52.30% and the photoelectric conversion efficiency is 7.80%.

[0090] Comparative Example 1

[0091] A method for preparing a flexible perovskite solar cell comprises the following steps:

[0092] (1) The ferritic stainless steel foil substrate was ultrasonically cleaned in anhydrous ethanol at 40° C. for 1 h, and then ultrasonically cleaned twice with deionized water, each time for 10 min, and finally dried in an oven at 70° C. for about 1 h and then taken out for use;

[0093] (2) loading the substrate into a magnetron sputtering device, and starting to sputter ITO or FTO when the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, the sputtering power is 200 W, the sputtering time is 10 min, the moving linear speed of the ferrite stainless steel foil substrate is 0.5-0.6 m / min, the argon gas flow rate is 20 sccm, and the argon gas pressure is 3 mTorr, completing the preparation of the bottom electrode;

[0094] (3) Place the bottom electrode with one side facing up in the drawer of a UV light cleaning machine. The UV light irradiation time is 15 minutes. The main wavelength of the UV light is 430nm. The power of the UV lamp is 250W. The UV light irradiation height is 20-40mm. Complete the UV activation treatment before the bottom electrode is coated.

[0095] (4) When the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, NiO sputtering begins. x The sputtering power is 140-160W, the sputtering time is 10 minutes, the component moving linear speed is 0.5-0.6m / min, the working gas is argon and oxygen mixed gas (oxygen accounts for 1%), the gas flow rate is 20sccm, and the gas pressure is 2mTorr to complete the preparation of the hole transport layer. Hole transport layer NiO x After the preparation is completed, it is placed in a 300°C oven for annealing for 1 hour, and then cooled to room temperature with the furnace and taken out;

[0096] (5) Slit-coat 0.8-1.5M CH3NH3PbI on the hole transport layer 3-x Cl x solution, the solvent is DMF, the injection speed is 0.1-0.2 ml / min, the coating gap is 0.2 mm, the coating head movement speed is 7 mm / s, and then the prepared perovskite film layer is annealed in an oven at 150 ° C for 10 min;

[0097] (6) Place the component in the chamber of the thermal evaporation deposition equipment. When the vacuum degree of the vacuum chamber is lower than 5*10 -4 Deposition begins at 0.2A / s at a rate of 0.2A / s. First, the electron transport layer C60 is deposited with a thickness of 5-15nm. Then, the electron transport layer BCP is deposited with a thickness of 5-15nm.

[0098] (7) Place the component in a magnetron sputtering chamber. When the vacuum degree of the magnetron sputtering chamber is lower than 0.00002 Torr, start sputtering ITO or FTO. The sputtering power is 150 W for 5 minutes, and then 200 W for 5 minutes. The component preparation is now complete.

[0099] Control test:

[0100] (1) The comparative example component was placed on a cylinder with a diameter of 50 and bent 100 times;

[0101] (2) The battery efficiency was tested using a Keithley 2450 digital source meter. The sweep voltage was set to 1.2 to 0.1 V, with a step of 0.1 V and an interval of 10 ms. The results are as follows: Figure 5 As shown, the open circuit voltage of the battery is 0.93V, the short circuit current density is 2.27mA / cm2, the fill factor is 28.75%, and the photoelectric conversion efficiency is 2.53%.

[0102] It can be seen that the battery prepared by the method for preparing a flexible perovskite solar cell provided in this application effectively utilizes the excellent mechanical properties of the ferrite stainless steel foil substrate and the absorption of the film stress by the borate modified material, and combines the excellent light absorption characteristics of the perovskite material to prepare a photovoltaic module with strong bending resistance and good mechanical properties, and higher photoelectric conversion efficiency, effectively overcoming the current problems of flexible perovskite solar cells being not resistant to high temperatures, poor stability, insufficient bending resistance, and poor mechanical properties, while also overcoming the problems of traditional rigid perovskite solar cells being heavy, large in size, unable to bend, narrow in application range, and inconvenient to transport. The overall preparation process is simple, energy consumption is low, and process repeatability is good, and flexible solar cell modules can be industrialized and mass-produced.

[0103] As shown in the figure, according to another aspect of the present application, a flexible perovskite solar cell is provided, which is prepared by any of the above-mentioned methods for preparing a flexible perovskite solar cell, and includes: a ferritic stainless steel foil flexible substrate, a bottom electrode, a hole transport layer, a perovskite light absorption layer, a borate modification layer, an electron transport layer and a top electrode arranged in sequence from bottom to top.

[0104] As an optional embodiment of the present application, optionally, the thickness of the ferritic stainless steel foil substrate is 35-50 μm; the thickness of the bottom electrode is 150-450 nm; the thickness of the hole transport layer is 10-50 nm; the thickness of the perovskite light absorption layer is 300-500 nm; the thickness of the borate modification layer is 5-20 nm; the thickness of the electron transport layer is 10-30 nm; and the thickness of the top electrode is 150-400 nm.

[0105] It should be noted that the battery structure in this embodiment is provided with a ferrite stainless steel foil flexible base, a bottom electrode, a hole transport layer, a perovskite light absorption layer, a borate modification layer, an electron transport layer and a top electrode from bottom to top, wherein the electron transport layer is a blend of C60 and BCP, and the thickness of the electron transport layer C60 is 5-15nm, and the thickness of the electron transport layer BCP is 5-15nm.

[0106] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing a flexible perovskite solar cell, characterized in that: The steps include: After the ferritic stainless steel foil substrate is subjected to a pre-plating treatment, a bottom electrode is deposited on the ferritic stainless steel foil substrate; After the bottom electrode is subjected to UV activation treatment before coating, a hole transport layer is deposited on the activated bottom electrode; Preparing a perovskite light absorbing layer on the hole transport layer; Slit coating a borate solution of a preset concentration on the upper interface of the perovskite light absorbing layer according to preset conditions to prepare a borate modified layer; preparing an electron transport layer on the borate modified layer; A top electrode is prepared on the electron transport layer to obtain a flexible perovskite solar cell.

2. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: In the borate solution, the borate is any one of MgB2O4, CaB2O4 and hydrates thereof, LiBO2, Li2B4O7, K2B4O7 and hydrates thereof, and the solvent is chlorobenzene.

3. The method for preparing a flexible perovskite solar cell according to claim 2, characterized in that: The preset concentration is 0.5-2 mg / ml.

4. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: The preset conditions include: The injection speed is 0.05-0.15ml / min, the coating gap is 0.2mm, and the coating head moving speed is 10mm / s.

5. The method for preparing a flexible perovskite solar cell according to claim 1, characterized in that: After preparing the borate modification layer by slit coating the borate solution on the upper interface of the perovskite light absorbing layer according to preset conditions, the method further comprises: The borate modified layer was annealed in an oven and then taken out.

6. The method for preparing a flexible perovskite solar cell according to any one of claims 1 to 5, characterized in that: The material of the ferritic stainless steel foil flexible substrate is 1Cr17 ferritic stainless steel foil.

7. The method for preparing a flexible perovskite solar cell according to claim 6, characterized in that: The materials of the bottom electrode and the top electrode are either ITO or FTO; The material of the hole transport layer is NiOx; The material of the perovskite light absorbing layer is CH3NH3PbI 3-x Cl x . The material of the electron transport layer is a mixture of C60 and BCP.

8. A flexible perovskite solar cell, prepared by the method for preparing a flexible perovskite solar cell according to any one of claims 1 to 7, characterized in that: include: The ferritic stainless steel foil flexible substrate, bottom electrode, hole transport layer, perovskite light absorption layer, borate modification layer, electron transport layer and top electrode are arranged in sequence from bottom to top.

9. The method for preparing a flexible perovskite solar cell according to claim 8, characterized in that: The thickness of the ferritic stainless steel foil substrate is 35-50 μm; The thickness of the bottom electrode is 150-450nm; The thickness of the hole transport layer is 10-50 nm; The thickness of the perovskite light absorbing layer is 300-500nm; The thickness of the borate modified layer is 5-20 nm; The thickness of the electron transport layer is 10-30 nm; The thickness of the top electrode is 150-400 nm.